PENINGKATAN KEMAMPUAN SISWA KOMPETENSI PRODUKTIF MENERIMA DAN MEMPROSES RESERVASI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KREATIF DAN PRODUKTIF SISWA KELAS XII PROGRAM KEAHLIAN AKOMODASI PERHOTELAN SMK NEGERI 1 MAGETAN TAHUN PELAJARAN 2015 / 2016 - Triwinarti, Anik (IKIP PGRI MADIUN, 2015)
Accepting and processing reservation competence is one of tourism field, both for education and tourism program. It gives the students skill, knowledge and attitude to act competence in doing front office job, especially as reservation officer. Creative and productive learning method has goal to create fun athmosphere in class since the students are not only able to learn theoritically, but also able to applied the theory in the real condition. The research method used is class action research. Population of this study are 36 students of XII (Aph1) Hotel Accomodation Majority. It is a descriptive research which the data is obtained by observation and test. Then the data is analayze by counting observation sheet using score formula.Â Â The result of this research is there is an increasing in teacher and students activity and the average grade in every cyclus.From the data, it is concluded that creative and productive method is able to increase the productive competence in accepting and processing reservation.Key Words: creative and productive method, students ability.